Leaf Retention Influences Photosynthetic Activities, LAI and PAR in Clone-2A Grapevine - Somkuwar, R. G.; Kakade, P. B.; Dhemre, J. K.; Gobade, N. J.; Karande, P. S.; Nikumbhe, P. H.; Deshmukh, N. A. (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during October, 2023 to March, 2024 at ICAR-National Research Centre for Grapes, Pune, Maharashtra, India to assess the leaf area requirement of Clone-2A grape variety. The experiment was laid out using Randomized Block Design (RBD) with variation in leaf on a fruit-bearing shoot such as 10,12,14,16 and >16 leaves above the bunch as five treatment replicated five times. The parameters measured were leaf area, leaf area index (LAI), photosynthetically active radiation (PAR), photosynthetic rate, stomatal conductance, chlorophyll content, average bunch weight, berry weight, yield vine-1, total soluble solids (TSS) and acidity. Maximum bunch weight (450.60 g), 50-berry weight (182.60 g), TSS (18.25°B) and yield vine-1 (19.46 kg) were recorded in 14 leaves shoot-1 above the bunch treatment. The highest photosynthetic activity such as assimilation rate (11.25 µmol CO2 m-2 s-1) and transpiration rate (2.85 mmol H2O m-2 s-1) and total chlorophyll content (35.28 mg ml-1) was observed in the same treatment. Minimum bunch weight (380.10 g), 50-berry weight (155.22 g), TSS (16.60°B) and yield vine-1 (16.38 kg) were observed in >16 leaves above the bunch treatment. However, retaining 14 leaves above the bunch in a shoot with 2861.42 cm2 leaf area shoot-1, 85842.60 cm2 leaf area vine-1 and 1988.00 cm2 leaf area bunch-1 were found sufficient for quality grape production in Clone-2A grape variety spaced at 9×5 ft2 distance.